Experimental research on the process of drying fuel chips from wood waste in a fixed bed - Liashenko, A. (Energy and Automation, 2023)
In Ukraine, wood production remains one of the priority sectors of the national economy. The total area of forests is 10.4 million hectares [1-3]. Scientific institutions and commercial organizations are constantly engaged in research and development of energy-efficient technologies and equipment for the utilization of organic waste (wood biomass) generated in forestry to solve primarily energy and environmental problems. Biomass is the fourth most important fuel in the world and currently replaces 1250 million tons of conventional fuel. It accounts for about 15% of the world’s primary energy sources. The advantages of biomass as a fuel are its renewable nature, low ash content, low emissions, and the preservation of the balance of carbon dioxide in the atmosphere [4]. Energy products of biomass processing can be used in common energy installations, for example, as a traditional fuel. One of the most common types of biomass of organic origin is wood. When decomposed into the main energy elements found in wood, we get about 50 % carbon, 6 % hydrogen, and 44 % oxygen. The calorific value of wood ranges from 14-17 MJ/kg. The Institute of Technical Thermophysics of the National Academy of Sciences of Ukraine (ITTF NASU) has been conducting research on various drying methods for a long time, as well as developing installations for heat treatment of fine labile materials. Studies have been conducted on drying and grinding green vegetation, clay, bark meal, industrial leather waste, etc. The studies show the prospects of using this drying method, the need to improve the design of plants for different materials, and the continuation of research on heat and mass transfer processes in them. The aim of the study is to experimentally determine the time required for dehydration of fuel chips during its drying in a fixed bed, depending on the temperature and speed of the coolant and the possible productivity of the designed new energy-saving drying plants. A series of experimental studies on convection drying of fuel wood chips on a laboratory bench called the "Fluidized bed drying bench" was carried out at the following thermal parameters temperature at the inlet of the working chamber varied from 130 °C to 180 °C; coolant velocity at the inlet of the working chamber - 0.3 - 1.2 m/s; material layer thickness - 100 mm; diameter of the working chamber - 135 mm; volume of the batch of material under study - 0.0014 m3; range of initial moisture content of the material under study (fuel wood chips) - from 46 % to 55 %; fuel wood chips had a volume content of shredded leaves - 10-20 %. In the future, the results obtained will form the basis for the development of new equipment and the creation of a methodology for engineering calculation of resource- and energy-efficient drying plants, which is the main task of further work and meets modern requirements for drying equipment. Key words: organic waste, biomass, utilization, forestry, drying plants, thermophysical properties, compatible process, engineering calculation